2019
DOI: 10.1089/dna.2018.4467
|View full text |Cite
|
Sign up to set email alerts
|

Genes Involved in the Processes of Cell Proliferation, Migration, Adhesion, and Tissue Development as New Potential Markers of Porcine Granulosa Cellular ProcessesIn Vitro: A Microarray Approach

Abstract: Proper course of folliculogenesis and oogenesis have an enormous impact on female fertility. Both processes take place in the ovary and involve not only the maturing germ cell, but also few types of somatic cells that assist the ovarian processes and mediate the dialog with the oocyte. These cells, granulosa and theca, are heavily involved in essential reproductive processes, such as ovulation, fertilization, and embryo implantation. In this study, we have used the expressive microarray approach to analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Previous studies have shown that the outer layer of granular cell ( GC ) is always above the basement membrane formed by collagen and laminin, and is protected by the follicular basement membrane from the primordial follicle stage to the dominant follicle selection stage of the final ovulation. The presence of laminin in the basement membrane may promote the growth and ovulation of the dominant follicle in follicular selection by enhancing the proliferation of GC ( Monniaux et al, 1999 ; Ożegowska et al, 2019 ). Cadherins, integrins, CAMs of the immunoglobulin superfamily, and selectins are considered the foremost CAMs classes ( Senderoff, 2013 ), among which N-cadherin plays an indispensable role in follicle formation, and its expression has been increasing during phase of developing follicles.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the outer layer of granular cell ( GC ) is always above the basement membrane formed by collagen and laminin, and is protected by the follicular basement membrane from the primordial follicle stage to the dominant follicle selection stage of the final ovulation. The presence of laminin in the basement membrane may promote the growth and ovulation of the dominant follicle in follicular selection by enhancing the proliferation of GC ( Monniaux et al, 1999 ; Ożegowska et al, 2019 ). Cadherins, integrins, CAMs of the immunoglobulin superfamily, and selectins are considered the foremost CAMs classes ( Senderoff, 2013 ), among which N-cadherin plays an indispensable role in follicle formation, and its expression has been increasing during phase of developing follicles.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Donadeu et al reported in a transcriptome profiling study that a large number of down-regulated DE genes in granulosa cells from horse ovarian follicles were enriched in the ECM during follicle dominance (Donadeu et al, 2014). Ożegowska et al also reported genes enriched in cell adhesion as new potential markers by analyzing the transcriptome of porcine granulosa cells (Ożegowska et al, 2019). The ECM and ECM protein form a complex scaffold of protein that provides the architectural support for cells.…”
Section: Discussionmentioning
confidence: 99%
“…Further analyses revealed five pathways in both comparisons: the intestinal immune network for IgA production, neuroactive ligand-receptor interaction, herpes simplex infection, phagosome, and calcium signaling pathways ( Figure 6). Moreover, a total of 28 differentially expressed genes, including genes related to ovary development, such as GH [16], ITGB3 [17], and TSHB [18], were detected in the five pathways ( Table 2). Some genes that may be important to ovary development, that is, PRL [19] and TGFB3 [20,21], were found in one of the two comparisons.…”
Section: Go and Kegg Pathway Enrichment Analyses Of Differential Genementioning
confidence: 99%